Strengthening Marketing Strategies To Support The Jadoel Lembah Si Cangkring Market To Become A Traditional Culinary Tourism Destination - Dwiarti, Rina; Lutiyan, Yetti; Arifin, Busthanul; Casmi, Eno; Fadhil Harfiez bin Abdul Muttalib, Mohd; Sumiyarsih, Sumiyarsih; Harsini Wahyuningsih, Tri (CV. Inara, 2023)
During the Covid 19 pandemic, it had a huge impact on all business sectors, including the Jadoel Valley Si Cangkring Market with its main business being traditional culinary tourism destinations. The Covid 19 pandemic also had an impact on decreasing sales turnover because few customers came. However, the opportunity and opportunity for Jadoel Valley Si Cangkring Market to develop business in the tourism sector is still open. This is because there are still a lack of tourist destinations that offer traditional products which can be the main attraction at Jadoel Market. Some of the products offered include: kricak porridge, megono rice, gudeg pecel, jadah tempeh, cucur, gatot, tiwul, wajik, to wiwit rice with shredded chicken as a side dish. Meanwhile, in the drinks section, wedang bajigur, dawet, bandrek, ice jadoel, brewed coffee, sekoteng, wedang uwuh and ginger and lemongrass palm sugar are available. The development of the Jadoel Lembah Si Cangkring Market in the last two years shows that the market or consumer reach is still limited to the community around Tempel sub-district and people who exercise by bicycle (goweser). Apart from that, traders are also still inadequate in serving consumers and are less able to read business opportunities which causes a lack of product innovation offered at each stall. Jadoel Lembah Si Cangkring Market has run promotions both online and offline, but tends to use offline marketing, namely Word of Mouth Marketing (WOMM), because it has limitations in mastering IT in online promotions.As for the results of the training that has been carried out, conclusions can be drawn: Si Cangkring Valley adopts good promotional methods, how to maintain consistency in developing tourist villages, how to maintain cohesion between managers, financial management, and much more. Si Cangkring Valley has great potential to be used as a traditional culinary tourism destination by using a marketing funnel. Lembah Si Cangkring can strengthen its marketing strategy with seven principles, abbreviated as DIGITAL. The principle in question is The Seven Laws which is an acronym for the 7 letters DIGITAL, namely: Differentiate products or services; simplify Ideas; Use creativity; Identify the position of customers or buyers in digital media; Keep what you promised; Align digital marketing strategy with organizational strategy; See what the market demand.